2018
DOI: 10.1063/1.5022759
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of anomalous Ettingshausen effect in a ferromagnetic film: Direct evidence of different symmetry from spin Peltier effect

Abstract: Spatial distribution of temperature modulation due to anomalous Ettingshausen effect (AEE) is visualized in a ferromagnetic FePt thin film with in-plane and out-of-plane magnetizations using the lock-in thermography technique. Comparing the AEE of FePt with the spin Peltier effect (SPE) of a Pt / yttrium iron garnet junction provides direct evidence of different symmetries of AEE and SPE. Our experiments and numerical calculations reveal that the distribution of heat sources induced by AEE strongly depends on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
91
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(100 citation statements)
references
References 31 publications
9
91
0
Order By: Relevance
“…11 Importantly, we found that the transient response of the SPE signal is different also from that of the AEE signal, although SPE and AEE are believed to exhibit the similar thermoelectric conversion symmetry in in-plane magnetized conditions. 17 To demonstrate the difference, we measured the f dependence of Aodd for AEE (gray circles) by using the sample in which the Pt/YIG layer is replaced with a 13.3-nm-thick Ni film, where the AEE signal appears in the Ni layer instead of the SPE signal.…”
mentioning
confidence: 99%
“…11 Importantly, we found that the transient response of the SPE signal is different also from that of the AEE signal, although SPE and AEE are believed to exhibit the similar thermoelectric conversion symmetry in in-plane magnetized conditions. 17 To demonstrate the difference, we measured the f dependence of Aodd for AEE (gray circles) by using the sample in which the Pt/YIG layer is replaced with a 13.3-nm-thick Ni film, where the AEE signal appears in the Ni layer instead of the SPE signal.…”
mentioning
confidence: 99%
“…For the measurements of the AMPE and the AEE, the slabs were cut into a U-shaped structure using wire electric discharge machining. The length along the x direction, total width along the z direction, width of the leg parts along the z direction, and thickness of the U-shaped slabs along the y We measured the temperature modulation induced by the AMPE and the AEE by means of the LIT method [18][19][20][24][25][26][27][28][29][39][40][41]. In the LIT measurements, while applying a square-wave-modulated AC charge current with the frequency f (1-25 Hz) to a sample, the temperature change oscillating with the same frequency as the charge current is extracted.…”
Section: Sample Preparation and Experimental Proceduresmentioning
confidence: 99%
“…This situation is being changed with rapid developments of spin caloritronics [24,32], where these phenomena are attracting renewed attention. In this stream, the observation of the anisotropic magneto-Peltier effect (AMPE) [37,41,45], the reciprocal of the AMSE, and the anomalous Ettingshausen effect (AEE) [39,[41][42][43], the reciprocal of the ANE, in ferromagnetic metals has recently been reported.The AMPE is a phenomenon that the Peltier coefficient depends on the angle θ M between the directions of a charge current J c and magnetization M in a ferromagnet. Due to the AMPE, the Peltier coefficient  in an isotropic ferromagnet exhibits the θ M dependence satisfying the following equation:where  ||() is the Peltier coefficient for the M || J c (M  J c ) configuration.…”
mentioning
confidence: 99%
“…The AEE generates a heat current in the direction of the cross product of J c and M:where j q,AEE , j c , m, and  AEE denote the heat-current density driven by the AEE, charge current density applied to a ferromagnet, unit vector of M, and anomalous Ettingshausen coefficient, respectively [ Fig. 1(a)] [39,[41][42][43].Therefore, when AEE is isotropic in a ferromagnet, the temperature gradient induced by the AEE should be proportional to sinθ M . The AEE may also bring novel thermal management technologies because it enables magnetic control of a heat-current direction.The understanding of the microscopic mechanism of the AMPE and AEE in ferromagnetic conductors and improvement of their thermoelectric conversion efficiency are crucial not only for the fundamental physics of spin caloritronics and thermoelectrics but also for the realization of nano-scale thermal energy engineering.…”
mentioning
confidence: 99%
See 1 more Smart Citation